(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
Insurance companies play a dual and vital role in the economy in which they operate in two directions. The first is to protect investments from the various risks that threaten them by paying compensation in the event of one of these risks, which prevents companies from leaving the economic cycle and achieving social benefit because of continuity of the company means continuity The payment of taxes to the state and the payment of salaries and wages to employees and employees, in addition to the economic ties in front and background, which integrate the company with other companies (that stop the company can lead to the cessation of other companies), the second trend is that the trap The insurance company obtains the amounts of insurance premiums in advance that become part of its ownership, enabling it to re-invest them in direct investments (insurance companies taking insurance premiums received in real estate or establishing industrial companies, etc.) or indirectly By investing premiums in the purchase of different types of securities) taking advantage of the period of time between receipt of installments and payment of compensation, which contributes to the provision of a source of funding to other companies and increase the profitability of insurance companies, thus achieving mutual benefit between the insurance sector and other sectors and vice versa The weakness of the performance of insurance companies, so the insurance sector in most countries of the most important sectors and wide because of the existence of a large number of risks faced by each company, which means paying more premiums for each risk that want insurance companies, which leads to the accumulation of large amounts in which contribute to pay Equity and refinancing of investments.